Essence of the monitoring system for managing project life cycle at an instrument-making holding - P. A. Zhurina; O. V. Tyagunova (Вестник университета)
The article examines the issues the monitoring system for managing project life cycle at an instrument-making holding project. The purpose of monitoring is to improve the project management system, identify discrepancies between actual and planned indicators, monitor the project indicators, change the organisation strategy development, proposals to eliminate potential threats. The main tasks adopted as monitoring-screening tools are the identification of key indicators; processing and aggregation of critically necessary information about specific project tasks; identification of external and internal risks; attractors that strongly influence the implementation of the project; issue of operational reports on the project; forecasting and decision-making, development of proposals to correct negative situations; ensuring the integration of the monitoring system in the information environment of the holding. The article reveals the key problems in this area and outlines conceptual directions for improving the process under study. The relevance of the material is the activity of a real specialist directly inside the dynamic structure of the holding, who knows all the old management methods and models new and redundant management methods, updating them in accordance with external and internal challenges. The experience of implementing the project of changing management paradigms during the crisis can be used to minimise further risks and accelerate the choice of effective management methods in organisations of large holdings, which, in turn, will allow you to reorient yourself as painlessly as possible to new management mechanisms that will contribute to more efficient operation of the holding as a whole.